Psilocybin and the Meaning Response: Exploring the Healing Process in a Retreat Setting in Jamaica - Orozco, Maria (Anthropology of consciousness, 2023)
In the past decade, the consumption of psilocybin mushrooms has become a popular therapeutic tool for people looking to deal with mental and emotional health issues. The emerging interest in psilocybin therapy in the global north has led to the development of retreat centers in locations where psilocybin is legal or unregulated. Drawing on ethnographic research at a psilocybin retreat center in Jamaica, this article examines the emotional and somatic reactions attributed to psilocybin that influence the social interactions and the mental and emotional state of the guests at this retreat center. We argue that guests go through a symbolic healing process that involves the construction of a meaning response based on internal and collective experiences of altered consciousness via psilocybin. Additionally, we emphasize how both attending the retreat and the psychedelic experience there can be considered a liminal state that leads to different modes of relation while in Jamaica.